The localization of luciferase in pteroptyx tener (coleoptera: lampyridae) light organ - Nur Khairunnisa S.,; Nurul Wahida Othman,; Norela Sulaiman, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Firefly is famously known for the light emission from its abdominal light organ. Light produce by firefly is known as bioluminescence. Luciferase is the enzyme that catalyze the light emitting reaction that produce bioluminescence. Haematoxylin and Eosin staining were used to describe the histological structure of the light organ. Localization of luciferase was discovered by immunohistochemical staining with polyclonal anti-luciferase and DAB chromogen as secondary antibody. Microphotography of light organ tissues was taken by Carl Zeiss Axio Scope A1 photomicroscope. This study revealed that the luciferase enzyme located at the photocyte cytoplasm of photogenic layer. This finding is an initial step to fully understand the regulation of synchronous light production in P. tener.